ETIKA PROFESI NOTARIS - Zaim, Mahibu; Tua, Hafizd Purbala; Jamaludin, Nurrun (al-Rasῑkh: Jurnal Hukum Islam, 2021)
One aspect that is highlighted in ethics and morals relating to one's behavior is a field of expertise called the profession. Because the profession as a job about theoretical and technical expertise, which relies on honesty, so the dependence and expectations of people who need help is very large to implement a good law enforcement system, so the profession is required to carry out the duties and functions of the profession, so he really works professionally in the field. Professionals engaged in the field of law include judges, prosecutors, police, advocates, notaries, and various elements of the institution authorized by law. To be a good organizer of the legal profession in carrying out its professional duties in upholding the law requires practitioners who have the qualifications of attitude, humanity, attitude of justice, able to see and place objective values in the cases handled, honest attitude, and the maturity of technical skills and ethics.